Rumble of the coaster ghost - Cummings, Troy (Cummings, Troy. Notebook of doom, 2016)
Alexander's class is going on a field trip to an amusement park called Safety Land with really slow, boring rides--but this is Stermont, and when a weird magician tells Alexander and his friends that the roller coaster is haunted things start to get a lot more interesting.